O Sapo Lambão e os cinco sentidos - Colosso, Cristiane Otília; Silva, Elenice da; Lima , Eliene Xavier de; Costa, Lucimeire de Souza; Silva , Luzinete Conceição da; Bento , Miriam Furtado; Schiavinato , Ricardo Leandro (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf